ROLE OF HOST COUNTRIES: HANDLING OF INDONESIAN ELECTORAL OFFENCES - Purnamasari, Andi Intan; Bin Mohd Zahir, Mohd Zamre; Md Said, Muhamad Helmi (Qaumiyyah: Jurnal Hukum Tata Negara, 2024)
This paper is based on the author's observations in several countries as places for the implementation of Indonesian elections abroad. as a host country, of course, the foreign country has a fundamental role in the implementation of Indonesian elections in that country. The voting design in the implementation of Indonesian elections abroad has a different mechanism between at home and abroad. The handling of criminal offence that occur in the case of Indonesian elections abroad, of course, also requires relations between foreign countries, namely the country where the Indonesian elections are held. Therefore, the contribution of foreign countries cannot be separated in handling election crimes. This article provides arguments based on normative analysis with a doctrinal approach to the applicable regulations on the role of foreign countries where Indonesian elections are held. The results of the election analyze conceptually, the role of foreign countries in the enforcement of Indonesian elections abroad. The region of the country where the Indonesian General Election is held abroad certainly plays a role in helping the smoothness of the voting process. For example, by adding assistance personnel for security during the implementation of voting. However, what is lacking is the norms or rules governing the role of the country and what assistance can be provided by the country where the implementation of the Indonesian elections abroad is incomplete, so it is necessary to make changes to the regulations on the General Elections of the Republic of Indonesia Abroad including the role of the country where the Indonesian overseas elections are held. Abstrak Tulisan ini didasarkan pada pengamatan penulis di beberapa negara yang menjadi tempat pelaksanaan pemilu Indonesia di luar negeri. Sebagai negara tuan rumah, tentunya negara asing memiliki peran yang fundamental dalam pelaksanaan pemilu Indonesia di negara tersebut. Desain pemungutan suara dalam pelaksanaan pemilu Indonesia di luar negeri memiliki mekanisme yang berbeda antara di dalam dan luar negeri. Penanganan tindak pidana yang terjadi dalam kasus pemilu Indonesia di luar negeri, tentunya juga membutuhkan hubungan antar negara asing, yaitu negara tempat pelaksanaan pemilu Indonesia. Oleh karena itu, peran negara asing tidak dapat dipisahkan dalam penanganan tindak pidana pemilu. Artikel ini memberikan argumentasi berdasarkan analisis normatif dengan pendekatan doktrinal terhadap peraturan yang berlaku mengenai peran negara asing tempat penyelenggaraan pemilu Indonesia. Hasil penelitian menganalisis secara konseptual peran negara asing dalam penegakan pemilu Indonesia di luar negeri. Namun yang menjadi kkekurangan adalah norma atau aturan yang mengatur tentang peran negara tersebut dan bantuan - bantuan apa saja yang dapat diberikan oleh negara tempat pelaksanaan pemilihan Indonesia di Luar negeri belum lengkap, maka memang perlu dilakukan perubahan terhadap peraturan tentang Pemilihan Umum Republik Indoensia di Luar Negeri termasuk juga peran negara tempat dilaksanakan pemilihan umum luar negeri Indonesia.